Production of Garbage Enzyme from Different Fruit and Vegetable Wastes and Evaluation of its Enzymatic and Antimicrobial Efficacy - Neupane, Karuna; Khadka, Rama (Tribhuvan University Journal of Microbiology, 2019)
Objectives: To evaluate the enzymatic and antimicrobial efficacy of enzyme from garbage produced from different fruits and vegetable wastes. Methods: This study was conducted from October-2018 to February-2019 in the laboratory of Padma Kanya Multiple College, Bagbazar, Kathmandu, Nepal. This study was carried for production, analysis of enzymatic and antimicrobial efficacy by using yeast (Saccharomyces cerevisae) and bacteria (Bacillus species) in 5 fruits peels, Mosambi (Citrus limetta), Pomegranate (Punica granatum), Pineapple (Ananas comosus), Papaya (Carica papaya) and mixed fruits collected from fresh fruit stall and vegetable peels collected from college’s hostel. The fermentation mixture was made in the ratio 1:3:10 (1 part brown sugar, 3 parts fruits/vegetable peels and 10 parts water) and left for 3 months for fermentation. Results: After fermentation, enzyme activity (amylase, protease, caseinase, cellulase and lipase) and antimicrobial efficacy (S. aureus, S. aureus (ATCC 25923), Bacillus spp, Salmonella Typhi, E. coli, E. coli (ATCC 25922), Shigella spp, Pseudomonas aeruginosa) were analyzed. All the samples showed amylase and caseinase enzyme activity, only Pineapple (Ananascomosus), Papaya (Carica papaya) and Mixed fruit showed protease enzyme activity while only Pomegranate (Punicagranatum) showed lipase enzyme activity. In antimicrobial efficacy test, garbage enzyme produced from vegetable sample didn’t show antimicrobial activity with bacteria used except E. coli (ATCC 25922)and S. aureus (ATCC 25923). Similarly, garbage enzyme produced from Mixed fruit and Papaya (Carica papaya) didn’t show antimicrobial activity with Salmonella Typhi and S. aureus (ATCC 25923) respectively but garbage enzyme from other wastes showed antimicrobial activity with bacteria used in test. Conclusion: Different fruits and vegetables wastes showed different enzyme activity and antimicrobial activity.